2012
DOI: 10.1007/s00415-011-6353-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebral activation after behavioral treatment for memory deficits in MS

Abstract: Deficits in new learning and memory are common in persons with multiple sclerosis (MS), though few studies have examined the efficacy of memory retraining in MS. Previous research from our laboratory has demonstrated that the modified Story Memory Technique (mSMT) significantly improves new learning and memory in MS. The present double-blind, placebo-controlled, randomized clinical trial was designed to examine changes in cerebral activation following mSMT treatment. Sixteen individuals with clinically definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
103
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 31 publications
5
103
0
1
Order By: Relevance
“…After rehabilitation, patients showed increased brain fMRI response only in the cerebellum when compared with healthy subjects. Few years later Chiaravallotti et al 26 explored changes in cerebral activation during the execution of a word learning and a word recognition task after a behavioural memory intervention, the modified Story Memory Technique. Greater activation was evident in the treatment group during performance of a memory task within a widespread cortical network involving frontal and temporal regions; no significant changes were found in the cerebellum.…”
Section: Imagingmentioning
confidence: 99%
“…After rehabilitation, patients showed increased brain fMRI response only in the cerebellum when compared with healthy subjects. Few years later Chiaravallotti et al 26 explored changes in cerebral activation during the execution of a word learning and a word recognition task after a behavioural memory intervention, the modified Story Memory Technique. Greater activation was evident in the treatment group during performance of a memory task within a widespread cortical network involving frontal and temporal regions; no significant changes were found in the cerebellum.…”
Section: Imagingmentioning
confidence: 99%
“…[25][26][27][28] This may be explained at least in part by several factors: lesions in "eloquent" brain areas such as the optic nerves are more likely to be clinically expressed than lesions in less eloquent pathways; the degree of matrix and axonal destruction may vary; and the potential exists for rapid symptom recovery. [29][30][31][32][33][34][35][36][37][38] Even patients with progressive forms of MS, particularly those with Gd+ lesions indicating a subclinical relapse, may respond clinically to disease-modifying therapies (DMTs). For example, in a post hoc analysis of the Olympus trial of rituximab in PPMS, patients with Gd+ lesions had a significantly better response to treatment than those without Gd+ lesions.…”
Section: Background Historical Evolution Of Ms Diagnostic Criteriamentioning
confidence: 99%
“…In agreement with the fact that the human brain can undergo plastic changes, several studies have shown that patients with MS experience a modulation of their activation patterns following structural tissue damage. [3][4][5][6] Such a functional reorganization mainly consists of increased activation of regions that are devoted to a given task and recruitment of additional areas that may or may not be part of the same network. These functional changes are thought to have a compensatory role, thus possibly explaining the weak relationship between MRI-detected tissue damage and patient clinical manifestations.…”
mentioning
confidence: 99%
“…4 Interestingly, studies in cognitive rehabilitation in MS are increasing and have shown functional changes of "critical" brain networks following rehabilitative intervention. 5,6 Resting-state fMRI may also be used to study MS and other neurologic conditions. At rest, specific neural networks are active, such as the so-called default mode and visual processing networks.…”
mentioning
confidence: 99%